Examining the Effects of Follistatin on Vessel Contraction - Sadat Afjeh, Seyedeh Niki (My University, 2024)
We have previously shown that short-term treatment (30 minutes) with follistatin (FST), a glycoprotein inhibitor of activins, reduced contraction caused by potassium (KCl) in vessels of the Spontaneously Hypertensive Rat (SHR) model of essential hypertension. This study specifically investigates the mechanisms through which FST inhibits KCl-induced vessel contraction in the SHR. Resistance mesenteric arteries taken from SHR or normotensive control WKY rats were tested in response to KCl using wire myography. Primary vascular smooth muscle cell (VSMC) cultures were established from WKY and SHR vessels. The fluorescent calcium sensor dye Fluo-4 AM and potassium tracking dye IPG-1 were then used to examine ion levels in the VSMCs. To determine whether FST effects were activin-mediated, neutralizing antibodies against activin A and B were used. Only activin A neutralization in the SHR reduced KCl-induced contraction as well as intracellular calcium rise, similarly to FST. Activin A (30 minute treatment) augmented KCl-induced contraction in both WKY and SHR vessels, but this was more pronounced in the SHR. There was an augmented KCl induced-intracellular calcium rise in SHR VSMC compared to WKY, which was decreased by FST. Inhibiting release of intracellular calcium stores did not attenuate KCl-induced calcium influx that was augmented by activin A or reduced by FST, but both of these effects were inhibited in calcium-free conditions. FST also significantly lowered the augmented KCl-induced intracellular potassium increase seen in SHR VSMC. Overall, FST reduces augmented KCl-induced contraction and rise in calcium and potassium levels in SHR vessels and VSMC. Taken together, these data suggest that FST may modulate L-type voltage gated Ca2+ channel (LTCC) or K-ATP channel activity. Neutralization studies support an important role for activin A, but not activin B, in mediating FST effects. Further studies will examine the mechanism by which FST modulates calcium influx.
Keywords: Hypertension; Resistance Vessels; Blood Pressure; Activins